Human immunodeficiency virus care cascade among sub‐populations in Rakai, Uganda: an observational study. Issue 1 (5th June 2017) - Billioux, Veena G.; Chang, Larry W.; Reynolds, Steven J.; Nakigozi, Gertrude; Ssekasanvu, Joseph; Grabowski, Mary K.; Ssekubugu, Robert; Nalugoda, Fred; Kigozi, Godfrey; Kagaayi, Joseph; Serwadda, David; Gray, Ronald H.; et al.
Abstract: Introduction : To assess progress towards the UNAIDS 90–90–90 initiative targets, we examined the HIV care cascade in the population‐based Rakai Community Cohort Study (RCCS) in rural Uganda and examined differences between sub‐groups. Methods : Self‐reports and clinical records were used to assess the proportion achieving each stage in the cascade. Statistical inference based on a χ 2 test for categorical variables and modified Poisson regression were used to estimate prevalence risk ratios (PRRs) and 95% confidence intervals (CI) for enrolment into care and initiating antiretroviral therapy (ART). Results : From September 2013 through December 2015, 3, 666 HIV‐positive participants were identified in the RCCS. As of December 2015, 98% had received HIV Counseling and Testing (HCT), 74% were enrolled in HIV care, and 63% had initiated ART of whom 92% were virally suppressed after 12 months on ART. Engagement in care was lower among men than women (enrolment in care: adjPRR 0.84, 95% CI 0.77–0.91; ART initiation: adjPRR 0.75, 95% CI 0.69–0.82), persons aged 15–24 compared to those aged 30–39 (enrolment: adjPRR 0.72, 95% CI 0.63–0.82; ART: adjPRR 0.69, 95%CI 0.60–0.80), unmarried persons (enrolment: adjPRR 0.84, 95% CI 0.71–0.99; ART adjPRR 0.80, 95% CI 0.66–0.95), and new in‐migrants (enrolment: adjPRR 0.75, 95% CI 0.67–0.83; ART: adjPRR 0.76, 95% CI 0.67–0.85). This cohort achieved 98–65–92 towards the UNAIDS "90–90–90" targets with an estimated 58% of the entire HIV‐positive RCCS population virally suppressed. Conclusions : This cohort achieved over 90% in both HCT and viral suppression among ART users, but only 65% in initiating ART, likely due to both an ART eligibility criterion of <500 CD4 cells/mL and suboptimal entry into care among men, younger individuals, and in‐migrants. Interventions are needed to promote enrolment in HIV care, particular for hard‐to‐reach sub‐populations.